A Study on Halal Supply Chain Awareness in Small and Medium Enterprise Towards Halal Certification in Indonesia - Roni Sahroni, Taufik; Idzni, Nadhila; Fajril, A. M.; Sri Ivan, M. (ExcelingTech, 2020)
Halal is a standard rule that could not be tolerated by the Muslim community. The increasing variety of products and foods in Indonesia is one of the background of the legislation on halal product assurance certification. It aims to provide the assurance status of the product to make society feel confident to buy and consume the products. Responding to the halal certification program which will be- realized in October 2019, the industry and society need to- know the supply chain for these products from the- manufacturing process to the storage process. This study was conducted by distributing 50 questionnaires to the food and beverage industry with the aim to determine the knowledge of the current industry needs and the awareness of the halal supply chain to participate in the certification program. The results showed, small-medium enterprise (SME) industry participants already understand the halal supply chain and halal certification but there are still many businesses have not registered and halal certified.